Trends in Autonomous Vehicles - Trajkoska, Vesela (My University, 2022)
This essay explains some of the current technological trends in autonomous vehicles. Most of the research is regarding the artificial intelligence of autonomous vehicle systems, but also considers strategies for proper tuning of sensors, algorithms for communication between vehicles and their energy efficiency. Some important research questions in the field of cybersecurity in autonomous vehicles are also listed. Finally, there is a comparison between three currently developed vehicle models. The general conclusion is that there is still no real autonomous vehicle, i.e. we are between the second and third level of automation (partial and conditional). It is also necessary to regulate the use of autonomous vehicles and to define procedures for when a system error occurs.